Risk of recurrence of cerebral venous and sinus thrombosis during subsequent pregnancy and puerperium. Issue 6 (1st June 2003) - Mehraein, S; Ortwein, H; Busch, M; Weih, M; Einhäupl, K; Masuhr, F
Abstract : Objective: To assess the risk of recurrence of cerebral venous and sinus thrombosis (CVST) during subsequent pregnancy and puerperium in women with previous cerebral venous occlusive disease. Methods: The authors retrospectively studied the relapse rate of CVST and the incidence of extracerebral venous thrombosis during subsequent pregnancies in 39 women (from 125 patients with CVST) who suffered a CVST at childbearing age. Results: Mean follow up was 10.25 years (range 1 to 20). Twenty two pregnancies and 19 births were observed in 14 women without evidence of either recurrence of CVST or extracerebral venous thrombosis. One pregnancy occurred during oral anticoagulation and was interrupted and two pregnancies ended with spontaneous abortions. Low dose heparin had been given during five pregnancies. Conclusions: The risk of recurrence for CVST during pregnancy seems to be low and these data do not justify a negative advice on pregnancy in women with previous CVST. Further studies are needed to evaluate the need for a prophylactic anticoagulation during pregnancy and puerperium.